Media Usee-Learning Scorm Standards In Increasing Teacher's Pedagogic Competence At SDN 008 Rokan IV Koto, Rokan Hulu District - Slamet Priono (Indonesian Journal of Basic Education, 2023)
Teachers have more limited time to improve their abilities than transferring material to students. It is hoped that by using the mediae-learning with SCORM standards, teacher competence can increase, so that the quality of students will indirectly improve. The purpose of this study was to determine differences in the ability of teachers to develop teaching materials on aspects of knowledge between those using the mediae-learning SCORM standard with modules. The method used in this research is a quasi-experimental designcontrol group pre-test post-test. The results of the study show that there is an influence on the use of mediae - learning SCORM standards for improving teacher pedagogic competence at SDN 008 Rokan IV Koto. Specifically, the conclusions are as follows: (1) Media usee-learning having a SCORM standard has a significant effect on the teacher's ability to develop teaching materials for knowledge aspects; (2) Use of mediae-learning having a SCORM standard has a significant effect on the teacher's ability to develop teaching materials for understanding aspects; (3) Use of mediae-learning SCORM standards have no significant effect on the teacher's ability to develop teaching materials for the application aspect